2005
DOI: 10.2174/157016105774329417
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin and the Ischaemic Heart

Abstract: IntroductionIt has been widely documented that plasma ET-1 and big ET-1 levels are increased in patients within a day of onset of acute myocardial infarction [1,2,3,4]. Similar changes in systemic plasma ET-1 are seen in animal models of myocardial ischaemia [5,6]. The source of the released ET-1 appears to be the area subjected to ischaemic damage, since in a study in anaesthetised pigs both short and long periods of left anterior descending (LAD) coronary artery occlusion were found to enhance overflow of ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 96 publications
1
26
0
1
Order By: Relevance
“…1, C and D). The Bay K 8644-induced increases in NPo of I CaL were completely reversed after 10-min washout with fresh bath solution (from 0.026 Ϯ 0.03 to 0.017 Ϯ 0.01, n ϭ 4, P Ͻ 0.05; the baseline NPo was 0.015 Ϯ 0.02) It has been shown that both ET A and ET B receptors are expressed in cardiomyocytes (Wainwright et al, 2005). Thus, we examined the endothelin-receptor subtype(s) involved in the L-type calcium current response to ET-1 by pretreatment of the cells with specific receptor antagonists.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…1, C and D). The Bay K 8644-induced increases in NPo of I CaL were completely reversed after 10-min washout with fresh bath solution (from 0.026 Ϯ 0.03 to 0.017 Ϯ 0.01, n ϭ 4, P Ͻ 0.05; the baseline NPo was 0.015 Ϯ 0.02) It has been shown that both ET A and ET B receptors are expressed in cardiomyocytes (Wainwright et al, 2005). Thus, we examined the endothelin-receptor subtype(s) involved in the L-type calcium current response to ET-1 by pretreatment of the cells with specific receptor antagonists.…”
Section: Resultsmentioning
confidence: 93%
“…It is also expressed in the heart and is released by endothelial, vascular smooth muscle, and myocardial cells, especially in cardiovascular disorders, such as congestive heart failure, cardiac hypertrophy, and ischemic heart disease (Moe et al, 2003;Angerio, 2005;Suzuki et al, 2005;Wainwright et al, 2005). Thus, it has been proposed that ET-1 plays a potential paracrine and autocrine role in cardiac functional and genetic regulation under pathophysiological conditions (Ito et al, 1991(Ito et al, , 1993Sugden, 2003).…”
mentioning
confidence: 99%
“…Additionally, it is well known that the endothelium plays an important role as a target of a variety of cardiovascular risk factors in a wide range of heart diseases, including atherosclerosis (43), angina (26), and ischemia (45,46). Vascular endothelial cells participate in cardiovascular regulation by producing several potent vasoactive agents, including the vasoconstrictor molecule ET.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin-1 exerts a wide variety of cardiovascular effects [1][2][3]. The consequences of these on the cardiac rhythm are currently under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of these on the cardiac rhythm are currently under investigation. They may be influenced by the concentration of ET-1, the species and cardiac chamber studied, the presence of adrenergic stimulation and the degree of any coronary vasoconstriction by ET-1 [1,3]. Endothelin-1 provoked arrhythmias in the ventricles, by prolonging action potentials and promoting afterdepolarisations, particularly in dogs in-vivo [4][5][6].…”
Section: Introductionmentioning
confidence: 99%